1993
DOI: 10.1089/aid.1993.9.715
|View full text |Cite
|
Sign up to set email alerts
|

Large Granular Lymphocytosis in a Patient Infected with HTLV-II

Abstract: HTLV-II has been associated with a variety of lymphoproliferative disorders, including atypical hairy cell leukemia, chronic T cell leukemia, T prolymphocytic leukemia, and large granular lymphocytic leukemia. However, a direct or indirect role for HTLV-II in these disorders is not yet firmly established. We studied a patient diagnosed as having leukemia of the large granular lymphocyte (LGL) type who was HTLV-II seropositive, to determine if the expanded cell population was infected. Two populations of CD3-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…8 Although other groups grated in the normal CD3 + CD8 + cells but not in the expanded neoplastic large granular cell population of NK phenotype report evidence for HTLV-I or -II infection in LGL leukemia (Table 2), there is only one case with convincing demon-(CD3 − CD16 + ). 29 In summary, our findings do not support a role for HTLV-I stration of clonal integration of either retrovirus in the neoplastic cells. 28 In this patient, a case of LGL leukemia was associaor -II in T-PLL or LGL leukemia.…”
Section: Reverse Transcriptase (Rt) Assaycontrasting
confidence: 81%
See 2 more Smart Citations
“…8 Although other groups grated in the normal CD3 + CD8 + cells but not in the expanded neoplastic large granular cell population of NK phenotype report evidence for HTLV-I or -II infection in LGL leukemia (Table 2), there is only one case with convincing demon-(CD3 − CD16 + ). 29 In summary, our findings do not support a role for HTLV-I stration of clonal integration of either retrovirus in the neoplastic cells. 28 In this patient, a case of LGL leukemia was associaor -II in T-PLL or LGL leukemia.…”
Section: Reverse Transcriptase (Rt) Assaycontrasting
confidence: 81%
“…29,[31][32][33][34] For example, in the largest study of HTLV-II in Again, in keeping with our results, two groups found no serological or molecular evidence of HTLV infection in LGL…”
Section: Reverse Transcriptase (Rt) Assaysupporting
confidence: 81%
See 1 more Smart Citation
“…38 The fact that transgenic mice for the HTLV-I tax gene develop NK cell LGL leukemia 39,40 and that sera from patients with both T-cell and NK cell LGL leukemia frequently react with HTLV-I/II p21 envelope proteins 41 had lead to the hypothesis of a direct relationship between CNKCL and infection by retroviruses. As in this series, cases of HTLV 42,43 or HIV-infected individuals 44 associated with CNKCL have been previously described. However, efforts to document association of CNKCL and infection with these 45,46 or other retroviruses 47 have been also unsuccessful.…”
Section: Discussionmentioning
confidence: 69%
“…Unlike HTLV-1, the related virus HTLV-2 has not been linked to human malignancies (33,55). HTLV-2, however, encodes a Tax protein (Tax2) which is highly homologous to HTLV-1 Tax (Tax1).…”
Section: Resultsmentioning
confidence: 99%